Quinoa Downy Mildew (Peronospora variabilis): A review on disease response and treatment - Chávez-Centeno, Víctor (2024)
Introduction. Quinoa downy mildew is a disease that causes economic losses and has been poorly studied.Therefore, researching quinoa’s response to the disease and treatment methods is a topic that requires further investigation. Objective. To describe how downy mildew infection affects quinoa plants and the non-traditional methods used to control this disease. Development. A systematic search was conducted to compile the results associated with P. variabilis in quinoa (Chenopodium quinoa Wild.) under various conditions. The analysis determined that factors such as incidence, severity, and disease tolerance depended largely on the quinoa grain variety and altitude (along with its climatic conditions). Plant height and yield per hectare were influenced by soil conditions, pest and disease treatment, and the planting day. Conclusions. The incidence and severity of downy mildew depended on the quinoa variety used. Other factors such as altitude or humidity also influenced disease progression, with infection rates close to 90 % in high humidity environments. Non-conventional methods for treating downy mildew included plant infusions such as chamomile and garlic, showing positive short-term results; however, they did not surpass conventional treatments with chemical fungicides.